Evolution of the macrostructure of gray cast iron from eutectic to hypereutectic composition - López, Marcos Gabriel (2018)
This work studies the evolution of the macrostructure of gray cast iron as the carbon equivalent (CE) increases from near-eutectic to highly hypereutectic values. The macrostructure of spherical samples of flake graphite irons of CE ranging between 4.24% and 5.23% was revealed by using direct austempering after solidification technique (DAAS). The results were analysed by applying the concept of coupled zone for gray cast irons. The coupled zone is a region in the stable Fe-C-Si diagram in which solidification proceeds as a cooperative growth of both austenite and flake graphite. The coupled zone for gray cast iron is claimed to be asymmetrical as the eutectic reaction is extended towards the prolongation of the austenite liquidus line. All the samples investigated in the present study show the presence of relatively large austenite grains, demonstrating that the number of active nucleation sites of austenite per unit volume is small. The observation of the microstructure shows the presence of several units of coupled growth inside each austenite grain, what proves that many eutectic colonies have grown from the same austenite nucleus, even for highly hypereutectic compositions. Colour etching was employed to reveal the “hidden” dendrites present in the microstructure. The results suggest that proeutectic graphite is not a good nucleating agent for austenite. These results contribute to the understanding of the solidification of hypereutectic gray irons and verify the earlier understanding of the solidification of eutectic gray irons and its extension to hypereutectic compositions.